Learning through Watching: Using Animation Movie to Improve Students’ Writing Ability - Dea Silvani (Journal of English Language Teaching and Linguistics, 2020)
Writing is often considered as a complicated skill to master. In order to be able to write effectively, there are several aspects to consider, which often make students face some problems in composing a written text. Thus, the use of the appropriate instructional media is necessary to help students overcome those problems, and enhance their writing ability. This classroom action research aims to investigate the improvement of students’ writing skill through the use of animation movie as the instructional media. The participants of this research were two observers and 38 second grade senior high school students. This research used observation as the technique of collecting the qualitative data about the teaching and learning process, which then analyzed by using thematic analysis. Meanwhile, writing tests were used to obtain the quantitative data about the students’ scores on the test given at the end of the cycles. Descriptive statistics are used to analyse the quantitative data obtained in  this study. The research result showed that their average scores increased from the pre-test (75.68), to the post test in cycle 1 (78.71) and the post- test in cycle 2 (83.55). It indicated that their writing skill was also increased. Therefore, the use of animation movie in English class can improve the second grade senior high school students’ writing skill.